Frontiers : histories of civil society and nature - Redclift, M. R. (MIT Press, 2006)
In Frontiers, Michael Redclift examines the relationship between nature and society in frontier areas--contested zones in which rival versions of civil society vie with one another, often over the definition and management of nature itself. Drawing on his own fieldwork and extensive archival research, Redclift presents five cases in which civil societies emerged in frontier areas either to manage common property or to legitimize private holdings: common-pool resource management in the Spanish Pyrenees, European settlement on the forest frontier in nineteenth-century Canada, conflicts over land and water resources in coastal Ecuador, Mayan civil unrest in the Yucatan peninsula, and the encroachment of tourism on the Mexican Caribbean coast. Redclift describes a dialectical process in frontier regions in which human societies and their environments influence and illuminate one another: the frontier can be seen as a crucible in which both nature and civil institutions develop and "co-evolve." In each of the five case studies, he argues, migration and land settlement gave rise to ideologies of nature that reflected not only the social and ethnic characteristics of the settlers but also the the effects of market forces on the natural environment. In most of these areas the natural environment was transformed by the pressure of the market, especially global markets. Resistance to market pressure created new avenues for political activity and the representation of cultural identity. Frontiers deepens and broadens our understanding of the role of the frontier, which, Redclift argues, needs to be considered within a global context that is of continuing importance today.